Allocative efficiency, plant dynamics and regional productivity: Evidence from Germany - Simon Bruhn; Thomas Grebel (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
This paper argues that regional variation in the efficiency of labor allocation among German manufacturing plants plays a critical role in explaining regional disparities in productivity. In fact, we show that over 50% of the East-West productivity gap is associated with a less efficient labor allocation in former East Germany. Yet, we also demonstrate that the mere focus on East-West comparisons hides partially large differences between the German federal states. These results suggest that regional productivity differences could be substantially narrowed by a more efficient labor allocation among plants. With respect to the underlying causes, we find evidence that the regional differences in allocative efficiency are significantly correlated with differences in export intensity, market concentration and plant size.
Keywords: E24; J24; L11; L25; O47; 330; Regional productivity gap; productivity decomposition; allocative efficiency; labor allocation